Testing and evaluation of full scale fiber-reinforced polymer bridge deck panels incorporating a polyurethane foam core. (1st April 2019) - Tuwair, Hesham; Drury, Jonathan; Volz, Jeffery
Highlights: FRP bridge deck that incorporates PU foam was developed for ABC and repair. Results of testing indicated that the deck significantly exceeded the AASHTO requirements. The decks behaved linearly-elastically throughout the full range of loading. The experimental results were used to evaluate the applicability of existing FRP design equations. Abstract: A fiber-reinforced polymer (FRP) bridge deck panel that incorporates a polyurethane foam core was developed for accelerated bridge construction and repair. This low cost panel was tested under monotonic loading and compared to applicable FRP design equations. This new prototype system consisted of two stiff facesheets of stitch bonded plain-weave woven E-glass fabric with sloping webs of E-glass woven fabric that are separated by trapezoidal-shaped, low-density polyurethane foam. The polyurethane foam was used in an attempt to reduce initial costs. The panels used in this study were manufactured using a one-step, vacuum-assisted, resin transfer molding process (VARTM) using a newly formulated, two-part, thermoset, polyurethane resin developed by Bayer MaterialScience to facilitate the infusion process. The results of the flexural and shear testing indicated that the prototype panels significantly exceeded the AASHTO Design Code Strength requirements by nearly three times. Even more importantly, the panels behaved linearly-elastically throughout the full range of loading and possessed significant post-buckling strength. In addition, the results of these full-scale panels were used to evaluate the applicability of existing FRP design equations when used for the design of the VARTM- manufactured, prototype FRP bridge deck. Results showed that the existing FRP design equations correctly predicted a flexural failure due to local buckling of the compression flange and a bearing failure due local buckling of the webs beneath the concentrated load.